FORENSIC LINGUISTICS: A BRIEF OVERVIEW OF THE KEY ELEMENTS - Jumaniyozova Nuriya Axmedovna, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article provides a concise yet comprehensive overview of forensic linguistics, a specialized field of applied linguistics that intersects with law and legal processes. It highlights the discipline’s key areas, including authorship attribution, legal language analysis, discourse examination, and speaker identification. The article also discusses the vital role of forensic linguists in both criminal and civil cases, particularly their contributions to the interpretation of confessions, legal documents, and digital communications. The growing importance of linguistic expertise in the pursuit of justice is emphasized, showcasing how forensic linguistics bridges the gap between language and law.